Asymptotic behavior of the solutions of boundary-value problems for singularly perturbed integro-differential equations - Dauylbayev, M. K.; Uaissov, A. B. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.928 We study the asymptotic behavior of the solutions of a boundary-value problem with boundary jumps for linear integrodifferential equations of the third order with small parameters at the two highest derivatives. The asymptotic convergence of the solution of a singularly perturbed integrodifferential boundary-value problem to the solution of the corresponding modified degenerate boundary-value problem is proved.